Scarcity And Free Shipping Effects on Impulse Buying of Skintific Skincare Consumers in Cirebon - Isma Nadiyah; Muhammad Santoso; Moh Yudi Mahadianto (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Purpose: The focal point of this scholarly inquiry is to empirically investigate the specific impact of scarcity marketing tactics and free shipping incentives on the impulse purchasing patterns of consumers. The study is contextually situated within the Shopee e-commerce ecosystem, specifically targeting the demographic of Skintific skincare product consumers located in the Cirebon region. Design/methodology/approach: From a methodological perspective, the research adopts a quantitative associative design to delineate the causal relationships between the proposed variables. Data acquisition was executed through the distribution of structured questionnaires to a purposive sample of 158 respondents who had previously engaged with Skintific products on Shopee and were exposed to the relevant promotional stimuli. The subsequent data processing and hypothesis testing were conducted utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), facilitated by the SmartPLS 4.1.1.6 computational software. Findings: Statistical analysis reveals that scarcity functions as a robust determinant of impulse buying behavior, confirmed by a path coefficient of 0.370, a t-statistic of 4.624 (>1.96), and a significance level of 0.000 (<0.05). In a parallel manner, free shipping promotions exert a positive and statistically significant influence on impulsive purchasing decisions, evidenced by a path coefficient of 0.167, a t-statistic of 2.369 (>1.96), and a p-value of 0.018 (<0.05). Collectively, the integration of scarcity and free shipping predictors elucidates 18.9% of the total variance in impulse buying behavior, as reflected by an R-Square value of 0.189. Research limitations/implications: The scope of this study is delimited to Skintific consumers within the Cirebon region and relies exclusively on two independent predictors. To augment the comprehensiveness and generalizability of future inquiry, it is recommended that subsequent research expand the conceptual framework to include additional variables, such as positive emotions, Fear of Missing Out (FoMO), and social media influence. Practical implications: From a practical perspective, these findings offer critical insights for e-commerce platforms and business practitioners in the formulation of digital marketing strategies. The study particularly underscores the strategic value of optimizing scarcity techniques, advocating for their deployment in an ethical and transparent manner to effectively stimulate consumer engagement. Paper type: Research paper